1989
DOI: 10.1128/jb.171.6.3228-3232.1989
|View full text |Cite
|
Sign up to set email alerts
|

The thiM locus and its relation to phosphorylation of hydroxyethylthiazole in Escherichia coli

Abstract: A mutant of Escherichia coli lacking hydroxyethylthiazole kinase (EC 2.7.1.50) was produced by a further mutation of a temperature-sensitive, auxotrophic mutant for hydroxyethylthiazole. The parent cells possessed two distinct enzymes capable of phosphorylating hydroxyethylthiazole: one was hydroxyethylthiazole kinase, and the other was a phosphotransferase species that required p-nitrophenylphosphate as a phosphoryl donor. Osmotic shock fluid prepared from the mutant cells phosphorylated hydroxyethylthiazole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 16 publications
1
25
0
1
Order By: Relevance
“…Thiamine from the growth medium is either phosphorylated by thiamine kinase or pyrophosphorylated by thiamine pyrophosphokinase (J. Melnick, E. Lis, J.-H. Park, H. Mori, C. Kinsland, J. Perkins, G. Schyns, A. Osterman, and T. P. Begley, submitted for publication). The pyrimidine and thiazole components can also be salvaged: thiazole is phosphorylated by thiazole kinase (2,4,6), HMP is phosphorylated to HMP-P by both ThiD and PdxK (3,7,10), and the phosphorylation of HMP-P is catalyzed by ThiD (5, 6, 7). Thus, ThiD has both a biosynthetic and a salvage function in thiamine biosynthesis.…”
mentioning
confidence: 99%
“…Thiamine from the growth medium is either phosphorylated by thiamine kinase or pyrophosphorylated by thiamine pyrophosphokinase (J. Melnick, E. Lis, J.-H. Park, H. Mori, C. Kinsland, J. Perkins, G. Schyns, A. Osterman, and T. P. Begley, submitted for publication). The pyrimidine and thiazole components can also be salvaged: thiazole is phosphorylated by thiazole kinase (2,4,6), HMP is phosphorylated to HMP-P by both ThiD and PdxK (3,7,10), and the phosphorylation of HMP-P is catalyzed by ThiD (5, 6, 7). Thus, ThiD has both a biosynthetic and a salvage function in thiamine biosynthesis.…”
mentioning
confidence: 99%
“…The thiazole moiety is thought to be derived from cysteine, tyrosine, and 1-deoxy-Dthreo-2-pentulose (10, 12, 17), while the pyrimidine moiety (HMP) is thought to be derived from aminoimidazole ribotide (AIR), an intermediate in purine biosynthesis (16, 18) and a proposed intermediate in the APB pathway (13). In E. coli, five kinases involved in TPP formation have been identified, and their genes have been mapped; thiL (min 10) encodes TMP kinase (22); thiK (min 25) encodes thiamine kinase (22); thiM, thiN, and thiD (min 46) encode THZ kinase, HMP kinase, and HMP-P kinase, respectively (22,27,28). Clearly, in E. coli and S. typhimurium, the genetic loci involved in thiamine synthesis are map throughout the chromosome (2, 31).…”
mentioning
confidence: 99%
“…0002-0837 0 1996 SGM close together on the chromosome at about 46 min (Mizote & Nakayama, 1989b). However, genetic analysis of HMP kinase (EC 2.7.1.49), which catalyses the phosphorylation of HMP to HMP-P, has not been possible because strains deficient in this enzyme have never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…One such mutant, strain SN372L-3-9-10, was used for further studies. To determine whether or not the transductants had received the tbiM mutation, HET kinase activity was assayed in cell extracts by the procedure described previously (Mizote & Nakayama, 1989b). The results showed that 31 of 39 tbij' transductants possessed only about 1 /20 to 1 /40 the HET kinase activity of strain SN372L-3-9-10, while in the remaining 8 thiJ'transductants the kinase activities were comparable to those of the recipient, showing that the thi] mutation is 78-80 % linked to the tbiM allele.…”
Section: Isolation and Characterization Of Thil Mutantmentioning
confidence: 99%